Antioxidant, Antimicrobial and Wound Healing Properties of Clinacanthus nutans (Burm. f.) Lindau and Strobilanthes crispus (L.) Blume Extracts - Weng Kit, Ban; Joyce Hui Yie, Phung; Isabel Lim, Fong; Khong, Heng Yen (Ban Weng Kit, 2023)
Clinacanthus nutans (C. nutans) and Strobilanthes crispus (S. crispus) both are well-known for their specific beneficial properties against different diseases. C. nutans is known to be anticancer and antiviral, especially against colon cancer, varicella-zoster virus, and herpes simplex virus. S. crispus has proven to be anti-diuretic and antidiabetic by multiple studies. In the previous studies, S. crispus extract showed promising results, capable of aiding in the wound healing process. Since C. nutans was commonly available as a balm in the traditional market, there is a high possibility that it contains antimicrobial and wound healing properties as well. Thus, this study aimed to confirm the medicinal benefits of C. nutans and S. crispus, specifically antimicrobial and wound healing properties. The C. nutans and S. crispus leaves were extracted with different polarity solvents; ethanol, acetone, and chloroform, through cold maceration and kept refrigerated at 2-8°C in the dark. The presence of phytochemicals, such as alkaloids, flavonoids, and saponin in the extracts were screened. These extracts were then assessed for their antioxidant potential by DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging assay using ascorbic acid as standard; determination of Total Phenolic Content (TPC) and Total Flavonoids Content (TFC) using Gallic Acid and Rutin as standard, respectively. Disk Diffusion Assay was performed to determine their antimicrobial properties. Modified scratch assay by co-incubating skin fibroblast with Methicillin-resistant Staphylococcus aureus (MRSA) and treated with the C. nutans and S. crispus extracts to determine their wound healing effects. These extracts were observed at 1, 3, 6, 10, 24, and 48 hours to investigate the cell migration activity depicting the closing up of wound. The phytochemical profiles for both C. nutans and S. crispus extracts were similar, except the C. nutans extracts have a higher saponin level compared with S. crispus extracts. The C. nutans acetone extract contained the highest level of antioxidant potential and TPC than the other C. nutans extracts. However, the ethanol extract of C. nutans showed the highest TFC, which was corresponded to the flavonoid content obtained from the phytochemical screening. The highest TPC value was recorded by the S. crispus ethanol extract, while the TFC test revealed similar pattern results among these S. crispus extracts. The C. nutans extracts showed a zone of inhibition of 14 to 16 mm when treated on Ps. aeruginosa, while S. crispus extracts showed distinctive zone of inhibition range between 11 to 15 mm on Ps. aeruginosa. There was no positive result observed when the extracts were treated on other bacteria. Fibroblasts were sensitive to acetone extracts, and S. crispus extracts were proven to have higher toxicity during the MTT assay. During the scratch assay with extracts only, C. nutans extracts showed wound healing properties, whereas S. crispus extracts seemed to be delayed the wound healing activity. However, when MRSA was added for the co-incubation, S. crispus extracts showed inhibition against the growth of MRSA and aided the wound healing activity, but this situation did not demonstrate in C. nutans extracts. The C. nutans and S. crispus extracts exhibited strong antioxidant and antimicrobial properties. C. nutans extracts aids in the wound healing activity, but if MRSA was involved, S. crispus extracts were capable of inhibiting the growth and aiding in the wound healing activity.